Self-Care Intervention in Post Sectio Caesarea Mothers - Khoirya, Ainun; Anggorowati, Anggorowati; Johan, Andrew (Universitas Islam Lamongan, 2022)
Post-SC mothers will usually experience a lack of self-care such as maintaining post-SC wound hygiene, breast care and early mobilization. The lack of self-care hygiene is caused by the presence of post-SC pain which can affect the physical activity that will be carried out on the mother, the lack of education during the short treatment. The purpose of this article is to determine the types of self-care interventions for self-care in post-SC mothers. In this article, we use Arksey and O'Melley models in analyzing. The literature sources used are through online databases, Science Direct, Pubmed, Google Scholar from 2017 to 2021. Identification and analysis using Preferred Reporting Items for Systematic Reviews and Meta Analysis for Scooping Review (PRISMA-SR). From the results of 5 articles that were analyzed, this article has summarized the types of self-care and education interventions used for self-care in post-SC mothers, including; early mobilization of post sectio caesarea with surgical wound healing, early mobilization with the level of independence of post sectio caesarea patients, knowledge of post-sectio caesarea (SC) wound care with the level of patient independence, communication, information, education (IEC) with mother's motivation in doing early mobilization post sectio caesarea, postpartum education with booklet media for mothers after sectio caesarea.